2001
DOI: 10.1163/156856201744425
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, biodegradation, and drug delivery application of biodegradable lactic/glycolic acid polymers. Part II: Biodegradation

Abstract: A series of previously-synthesized lactic/glycolic acid polymers (PLGA) with various molar ratios of lactic to glycolic acid and various molecular weights were further studied with regard to their biodegradation behavior, and in particular, the factors affecting the biodegradation rate. The biodegradation of PLGA is affected by many factors including polymer composition, molecular weight, and nature of the incubating media. The biodegradation rate of PLGA containing higher content of lactic acid moiety is lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
135
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(147 citation statements)
references
References 15 publications
8
135
0
4
Order By: Relevance
“…The degradation rate of PLGA microspheres can be influenced by the polymer composition, preparation conditions, and the incorporation of additives (22)(23)(24). For example, it has been shown that the inclusion of BSA facilitates the release of growth factor from a polymer matrix (25).…”
Section: Discussionmentioning
confidence: 99%
“…The degradation rate of PLGA microspheres can be influenced by the polymer composition, preparation conditions, and the incorporation of additives (22)(23)(24). For example, it has been shown that the inclusion of BSA facilitates the release of growth factor from a polymer matrix (25).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of drug release is determined primarily by the matrix hydrolysis rate and the ability of the drug to diffuse through the generated spaces. PLGA molecules with higher lactide content degrade at a slower rate than lower lactide content polymers (12). Thus, microspheres with higher lactide content may release GCV at a slower rate relative to PLGA molecules with lower lactide content.…”
Section: Theorymentioning
confidence: 99%
“…A number of other properties that have been shown to affect the eventually developed (resulted) tissue, involve, but are not restricted to, chemical composition and architecture of the scaffold, its porosity and pore size, hydro-phobicity, and charge. PLGA (poly lactic-coglycolic acid) is a type of synthetic polymer with the characteristics of biocompatibility, low immunogenicity, and absolute biodegradability; it can also be processed into any shape and size, and encapsulate molecules of virtually any size (Uhrich et al 1999;Wu & Wang 2001;Makadia & Siegel 2011). A fibrin scaffold is known as a network of protein that together protects different kinds of living tissue.…”
Section: Introductionmentioning
confidence: 99%